A Concept for Selection of Codon-Suppressor tRNAs Based on Read-Through Ribosome Display in an In Vitro Compartmentalized Cell-Free Translation System - Ogawa, Atsushi; Hayami, Masayoshi; Sando, Shinsuke; Aoyama, Yasuhiro (Journal of Nucleic Acids, 2012)
Here is presented a concept for in vitro selection of suppressor tRNAs. It uses a pool of dsDNA templates in compartmentalized water-in-oil micelles. The template contains a transcription/translation trigger, an amber stop codon, and another transcription trigger for the anticodon- or anticodon loop-randomized gene for tRNASer. Upon transcription are generated two types of RNAs, a tRNA and a translatable mRNA (mRNA-tRNA). When the tRNA suppresses the stop codon (UAG) of the mRNA, the full-length protein obtained upon translation remains attached to the mRNA (read-through ribosome display) that contains the sequence of the tRNA. In this way, the active suppressor tRNAs can be selected (amplified) and their sequences read out. The enriched anticodon (CUA) was complementary to the UAG stop codon and the enriched anticodon-loop was the same as that in the natural tRNASer.